Optimization of the Quality of Medan City Local Government Financial Reports Based Accounting Understanding Method - Marlina; Renny Maisyarah (International Journal of Economic, Technology and Social Sciences (Injects), 2024)
This study aims to analyze the effect of accounting understanding on optimizing the quality of financial reports of the Medan City Regional Government simultaneously and partially. where the quality of financial reports in accordance with Government Accounting Standards (SAP) is very important to create transparency, accountability, and public trust in regional financial management. This research method uses a quantitative approach with primary data collected through questionnaires to regional financial management officials in Medan City. Data were analyzed using the regression method to measure the relationship between the level of accounting understanding and the quality of financial reports. The variables tested include mastery of basic accounting principles, application of SAP, and technical skills in preparing financial reports. where the study shows that accounting understanding has a positive and significant effect on the quality of financial reports. Apparatus who have a good level of accounting understanding tend to produce financial reports that are more accurate, relevant, accountable, and in accordance with SAP. However, there are several obstacles that affect these results, such as the lack of ongoing training and limited human resources who are competent in the field of accounting. optimizing the quality of financial reports of the Medan City Regional Government can be achieved by increasing accounting understanding by government officials.